Smartphone Dependency and Its Impact on Emotional Fatigue: Mediated by Sleep Disturbance - Chen, Daniel; Mehta, Rakesh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to investigate the impact of smartphone dependency on emotional fatigue among Indian university students, with sleep disturbance examined as a potential mediating variable. Methods and Materials: The study employed a descriptive correlational design involving 433 participants selected based on the Morgan and Krejcie sampling table. Standardized tools were used to measure the variables: the Smartphone Addiction Scale–Short Version for smartphone dependency, the Pittsburgh Sleep Quality Index for sleep disturbance, and the Emotional Exhaustion subscale of the Maslach Burnout Inventory–General Survey for emotional fatigue. Data analysis included Pearson correlation using SPSS-27 to assess bivariate relationships, and Structural Equation Modeling (SEM) via AMOS-21 to test direct and indirect effects and evaluate model fit. All assumptions for correlation and SEM, including normality, linearity, and absence of multicollinearity, were confirmed prior to analysis. Findings: The results indicated that smartphone dependency was significantly correlated with both sleep disturbance (r = .51, p < .001) and emotional fatigue (r = .48, p < .001), and that sleep disturbance was significantly associated with emotional fatigue (r = .56, p < .001). SEM analysis showed that smartphone dependency had a significant direct effect on sleep disturbance (β = .51, p < .001) and emotional fatigue (β = .23, p = .005), while sleep disturbance also had a significant direct effect on emotional fatigue (β = .46, p < .001). The indirect effect of smartphone dependency on emotional fatigue via sleep disturbance was also significant (β = .23, p < .001), confirming partial mediation. The model fit indices indicated good model fit (χ²/df = 2.28, CFI = .97, RMSEA = .054). Conclusion: The findings highlight the detrimental effects of smartphone dependency on emotional fatigue, both directly and indirectly through its impact on sleep disturbance, suggesting the need for targeted interventions to manage digital behaviors and promote healthy sleep among young adults.